ATL. Issue 7 (1st September 2014) - Liang, Xiaolong; Liu, Yi; Zeng, Liqiong; Yu, Chao; Hu, Zhongwen; Zhou, Qin; Yang, Zhu
Abstract : Objectives: The chief objective of this study was to identify the miRNAs targeting Fos, a well-recognized proto-oncogene that is commonly overexpressed in cervical cancer, and its biological significance on the cellular behaviors of HeLa, a cervical cancer cell. Materials and Methods: We initially analyzed the 3′untranslated region (3′UTR) of Fos and screened the potential miRNAs targeting Fos using 3 bioinformatical Web sites. Luciferase reporter assay, real-time polymerase chain reaction, and Western blotting were used to validate the binding of chosen miRNA (miR-101) on the 3′UTR of Fos and the downstream regulation on its mRNA and protein levels. Furthermore, flow cytometry along with the Fos rescue strategy was applied to analyze the modulation of cell cycle of HeLa cells by miR-101. Results: Among these predicted candidate miRNAs, miR-101 was the miRNAs preferred by all the 3 used Web sites. The results of luciferase reporter assay, real-time polymerase chain reaction, and Western blotting demonstrated that miR-101 directly targeted on the 3′UTR of Fos and down-regulated the expression of Fos at mRNA and protein levels. Furthermore, cell cycle analysis showed that miR-101 arrests G1-to-S phase transition of HeLa cells, at least partially by targeting Fos . Conclusions: We concluded that by targeting the proto-oncogene Fos, miR-101 is involved in G1-to-S phase transition in cervical cancer cells in vitro and might provide a new approach for the pharmacological interference node in cervical cancer treatment.